(untitled) (International Journal of Environmental Sciences, 2025)
The lack of qualified caretakers in assisted living institutions has been made worse by the COVID-19 epidemic, which has led to an investigation into technology to address the increasing care requirements of residents. One strategy that may improve older folks’ care and the professional lives of those who provide it is the use of care robots. However, there are still some issues with the best practices, ethics, and efficacy of using robotic technology in care facilities. The purpose of the scoping study was to assess the body of research on robots in assisted care institutions, find any gaps, and guide future studies. 73 papers from 69 investigations on the employment of robots in these settings were examined in the review. Some elderly persons expressed concerns about robots and access restrictions, while others reported possible benefits of robotics. The results of the study were mixed. Even though care robots have demonstrated therapeutic benefits, the studies’ internal and external validity were weakened by methodological flaws, underscoring the need for more thorough research approaches. Large sample sizes, longitudinal studies, and theory-based research approaches were uncommon. It is difficult to aggregate and assess care robotics research due to inconsistent methodological quality and reporting across the authors’ areas.